EFFORTS TO INCREASE CHILDREN'S LANGUAGE CREATIVITY IN THE METHOD OF STORYING THROUGH THE FINGER PUP IN RA MUSLIMAT NU DOLOGAN, KEC. JAPAH, KAB. BLORA - Istikomah, Nuzulul; Mufid, Abdul (Journal of Industrial Engineering & Management Research, 2021)
- This study aims to determine children's language and strengthen children's creativity in learning to socialize. The method that the author uses is a literature review method with a storytelling method approach using finger puppet media. The research question that will be answered is how to increase children's language creativity in the storytelling method through finger puppet media? Based on the results of the research that the authors have done, it can be concluded that the method of teaching children through finger puppet media can improve children's language skills creatively. So that children in the ability to read and process words to speak can be done easily.